Gene synthesis allows biologists to source genes from farther away in the tree of life. Issue 1 (December 2018) - Kunjapur, Aditya; Pfingstag, Philipp; Thompson, Neil
Abstract Gene synthesis enables creation and modification of genetic sequences at an unprecedented pace, offering enormous potential for new biological functionality but also increasing the need for biosurveillance. In this paper, we introduce a bioinformatics technique for determining whether a gene is natural or synthetic based solely on nucleotide sequence. This technique, grounded in codon theory and machine learning, can correctly classify genes with 97.7% accuracy on a novel data set. We then classify ∼19, 000 unique genes from the Addgene non-profit plasmid repository to investigate whether natural and synthetic genes have differential use in heterologous expression. Phylogenetic analysis of distance between source and expression organisms reveals that researchers are using synthesis to source genes from more genetically-distant organisms, particularly for longer genes. We provide empirical evidence that gene synthesis is leading biologists to sample more broadly across the diversity of life, and we provide a foundational tool for the biosurveillance community. Gene synthesis has expanded the ability to modify and create DNA sequences, with implications for biosurveillance. The authors use machine learning and codon theory to identify synthetic genes in Addgene data, and show that synthesis accelerates human-directed gene transfer across the tree of life.